Sedative and Immunosuppressive Effects of Dexmedetomidine in Transplantation - Chen-Fang Lee; Chih-Hsien Cheng; Hao-Chien Hung; Jin-Chiao Lee; Yu-Chiao Wang; Tsung-Han Wu; Ting-Jung Wu; Hong-Shiue Chou; Kun-Ming Chan; Wei-Chen Lee (MDPI AG, 2021)
Dexmedetomidine, an α2-adrenergic receptor agonist, is used as an anti-anxiety medication. It exerts a cholinergic effect, thereby reducing the release of tumor necrosis factor alpha (TNF-α). We hypothesized that the use of dexmedetomidine as a sedative agent in transplantation would also protect allografts. We examined our patients who underwent living donor liver transplantation. Subsequently, we generated a series of mouse models to investigate the effect of dexmedetomidine on sedation-based tolerance post transplantation. A total of 49 liver recipients were enrolled in this study, of which 23 (47%) were administered dexmedetomidine through 24 h infusion on postoperative day 1. A trend toward the improvement of hepatocyte injury along with better liver function was observed in the dexmedetomidine-treated group during the first postoperative week. In animal models, dexmedetomidine inhibited the proliferation of CD4+ and CD8+ T cells and TNF-α production in a dose-dependent manner. We used dexmedetomidine to treat skin-transplanted mice and observed a significantly prolonged graft survival in mice that were administered a higher dose of dexmedetomidine. Our results revealed that dexmedetomidine exerts a dual effect of sedation and immunosuppression. This light-sedation approach will not only make patients calmer in the intensive care unit but also protect allografts from injury.